Plastic foreign body appearing as radiopaque in a child: An interesting case - Aditya Pratap Singh; Ramesh Tanger; Arun Kumar Gupta; Rajlaxmi Pardeshi (Wolters Kluwer Medknow Publications, 2019)
Accidental and unnoticed ingestion of foreign bodies (FBs) is not very uncommon. Most of such FBs pass through the gastrointestinal tract uneventfully and only on rare instances cause obstruction or perforation. We present here a case of unnoticed ingested plastic FB in an 11-month-old male child. The baby was presented to us with the complaint of acute intestinal obstruction. The plastic FB appeared as a radiopaque ring in the plain erect abdominal X-ray. The patient was managed by only sodium phosphate enema, which expelled the FB out through the anus.